HIDROLISIS PATI KACANG TOLO (Vigna unguiculata) DENGAN ENZIM Î±-AMILASE DAN APLIKASINYA SEBAGAI MIKROENKAPSULAN ASAP CAIR - , DESINTHA IKA SAVITRI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Cowpea is one of the type of nuts which is utilization was limited, but contains high levels of starch. The starch from cowpea can be processes into maltodextrin using enzymatic method which can be applied as encapsulant. Liquid smoke can be used to replace the traditional curing process. Liquid smoke contain phenolicâs compounds, acids and carbonyls. This compounds are easily lost during storage. Encapsulation process is used to protect this compounds. Production of maltodextrin used Î±-amylase enzymes with variation of hydrolysis times are 60 minutes, 90 minutes, and 120 minutes to know optimal hydrolysis time. Liquid smoke microencapsulationâs method used in this study is spray drying. In this study, liquid smoke encapsulated with maltodextrin as coating materials which is the variation ratio of liquid smoke solid and maltodextrin are 1 : 2, 1 : 3,5, and 1 : 5. The result of microcapsules were analyzed these efficiency and characteristics. The result showed that the highest solubility in three time variationâs is not different. So, hydrolysis time 60 minutes is choosen. Ratio variation of liquid smoke and maltodextrin can affect the efficiency and characteristics of liquid smoke microcapsule. The optimum ratio variation of liquid smoke and maltodextrin in microencapsulation process was 1 : 5.